Two new species of Protonemura Kempny, 1898 (Plecoptera: Nemouridae) from the Italian Alps - Vinçon, Gilles; Reding, Jean-Paul G.; Ravizza, Carlalberto (Zootaxa, 2021)
Two new species of Protonemura Kempny, 1898, P. bispina sp. n. and P. pennina sp. n., from the Eastern and Western Italian Alps, respectively, are described and illustrated. Further information on distribution and ecological preferences of these new species is provided. The species Protonemura auberti Illies, 1954 is re-described from topotypical material.